THE PROBLEM OF ABANDONED PROPERTY AFTER THE ENTRY INTO FORCE OF THE DECREE ON OWNERSHIP AND USE OF LANDS IN THE CAPITAL CITY OF WARSAW - Abramowska, Monika (Management and Administration Journal, 2022)
This article attempts to answer the question of whether abandoned property existed in Warsaw after the entry into force of the Decree on Warsaw Lands. Contemporary case law is consistent in the position that within the territory of the capital of Poland, after the entry into force of the Decree on Warsaw Lands, there was no abandoned property given the categorical wording of Article 1 of the Decree that on the date of entry into force, all Warsaw lands are transferred to the municipality of the Capital City of Warsaw. However, post-war doctrine is of the opinion that for the transfer of ownership it was necessary to enter the new owner in the land and mortgage register.